Work ability, psycho-physical health, burnout, and age among nursery school and kindergarten teachers: a cross-sectional study - Converso, Daniela; Viotti, Sara; Sottimano, Ilaria; Cascio, Vincenza; Guidetti, Gloria (La Medicina del Lavoro, 2015)
Introduction: Although well-being and psychophysical health of nursery school and kindergarten teachers have important implications also on the health and well-being of their recipients, studies dedicated to these workers are quite rare, particularly in Italy. Aim: The aim of the study was to observe psychophysical health conditions in a sample of nursery school and kindergarten teachers employed in the Education Services Division of the Municipality of Turin. Method: The study was cross-sectional; 884 self-reporting questionnaires were distributed and 734 teachers (representing 53% of those employed at the Education Services of the Municipality of Turin) correctly filled out the questionnaire. Results: Respectively 53.4% and 50% of participants reported medium or high levels of emotional exhaustion and depersonalization, while 18.5% showed low levels of personal accomplishment. Responders reported moderate levels of work ability in 38.9% and poor levels in 5.6%. The majority of the respondents (98.7%) did not report depressive symptoms; 42.9% of the sample suffered moderate to severe limiting musculoskeletal pain. Age and profession were associated with emotional exhaustion, personal accomplishment, and musculoskeletal pain. However, work ability and depression were only associated with age. No associations were found with depersonalization. Conclusions: The present study shows that health conditions of nursery school and kindergarten teachers were critical and that age contributed to the explanation of these conditions.